Strategi Pengembangan Potensi Pariwisata Kawasan Benteng Moraya di Kabupaten Minahasa - Merensia Rawung (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
The title of this research is the Development Strategy of the Tourism Potential of the Moraya Fort in Minahasa Regency. This study analyzes the current state of the Moraya Fortress Tourism Area, explains the supporting and inhibiting factors for the development of the Moraya Fort area, and analyzes the most appropriate strategy for the development of the Moraya Fort area in Minahasa Regency. The research method used is qualitative research methods, with data sources Person, Place, and Place. Furthermore, a SWOT analysis is carried out to obtain the right strategy. The research results show that the current condition of the Moraya Fort area is still lacking and needs improvement and additions both related to the Moraya Fort area and its supporting facilities. For this reason, the researchers found several strategies that they felt could help the development of the Moraya Fort area.